2010
DOI: 10.1161/atvbaha.110.203588
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis in Abdominal Aortic Aneurysms: A Causal Event or a Process Running in Parallel? The Tromsø Study

Abstract: The lack of a consistent dose-response relationship between atherosclerosis and abdominal aortic diameter suggests that atherosclerosis may not be a causal event in AAA but develops in parallel with or secondary to aneurismal dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 31 publications
4
78
0
2
Order By: Relevance
“…AAA has traditionally been thought to be caused by atherosclerosis. Recently, this atherosclerosis theory has been challenged on the basis of epidemiologic, genetic and biochemical information, questioning whether atherosclerosis is a "bystander" condition or an active participant in the development and progression of AAA disease Johnsen et al, 2010;Lee et al, 1997;Reed et al, 1992;Trollope & Golledge, 2011). As seen in previously described studies on AAA prevalence in CAD patients, not all patients with atherosclerotic disease do present an AAA.…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…AAA has traditionally been thought to be caused by atherosclerosis. Recently, this atherosclerosis theory has been challenged on the basis of epidemiologic, genetic and biochemical information, questioning whether atherosclerosis is a "bystander" condition or an active participant in the development and progression of AAA disease Johnsen et al, 2010;Lee et al, 1997;Reed et al, 1992;Trollope & Golledge, 2011). As seen in previously described studies on AAA prevalence in CAD patients, not all patients with atherosclerotic disease do present an AAA.…”
Section: Pathophysiologymentioning
confidence: 99%
“…However, recent case control studies did not find any evidence for more carotid atherosclerosis in AAA patients (Cheuk et al, 2007;Palazzzuoli et al, 2008). In an attempt to better elucidate this relationship, Johnsen et al reported significantly more carotid atherosclerosis in abdominal aortic aneurysm diameter  27 mm and in AAA (Johnsen et al, 2010). Among CAD patients, 5 studies appraised an association between AAA and PAD, while the association between AAA and CAS was analyzed in only 4 studies (table 5).…”
Section: Concomitant Vascular Disease To Abdominal Aortic Aneurysm Anmentioning
confidence: 99%
“…AAA and atherosclerotic CVD share common risk factors such as smoking and elevated blood pressure or cholesterol levels, and often co-exist. However, AAA and CVD may develop in parallel through different pathogenic mechanisms, with weakening of the aortic wall playing a key role in aortic dilation and AAA formation (7). Changes in the walls of aneurysmal aortas are characterised by up-regulation of proteolytic pathways, the loss of matrix, inflammation and, to a variable extent, atherosclerosis (22).…”
Section: Discussionmentioning
confidence: 99%
“…Aortic diameter is a marker of global cardiovascular risk even in the absence of an AAA. Increasing age and male gender are key risk factors for AAA (7). IGF1, IGF1 receptors and IGFBPs are expressed in vascular smooth muscle cells (VSMC) of human atherosclerotic plaques (8), and lower circulating levels of IGF1 have been associated with the incidence of cardiovascular events and stroke in previous studies (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…As such, it was presumed that both entities were the result of extensive atherosclerosis [1]. This assumption was largely based on the fact that the two vascular diseases share a number of risk factors, such as smoking, hypertension, and older age [2e6].…”
Section: Introductionmentioning
confidence: 99%